2021
DOI: 10.3390/antibiotics10020109
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Stress-Induced Phenolic Metabolites for Antimicrobial Applications against Foodborne Human Bacterial Pathogens

Abstract: Foodborne bacterial pathogens in consumed foods are major food safety concerns worldwide, leading to serious illness and even death. An exciting strategy is to use novel phenolic compounds against bacterial pathogens based on recruiting the inducible metabolic responses of plant endogenous protective defense against biotic and abiotic stresses. Such stress-inducible phenolic metabolites have high potential to reduce bacterial contamination, and particularly improve safety of plant foods. The stimulation of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…The mechanism of antimicrobial activity of phenolic phytochemicals is due to their ability to permeabilize the microbial cell membrane, inhibit DNA or protein synthesis, inhibit microbial metabolic activity, as well as chelate compounds required for microbial growth [ 58 61 ]. The antimicrobial activity observed in the current study clearly suggests that these selected botanicals, especially amla and kokum with their high baseline phenolic content, are good bioactive ingredients to counter bacterial contamination of other plant-based foods.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of antimicrobial activity of phenolic phytochemicals is due to their ability to permeabilize the microbial cell membrane, inhibit DNA or protein synthesis, inhibit microbial metabolic activity, as well as chelate compounds required for microbial growth [ 58 61 ]. The antimicrobial activity observed in the current study clearly suggests that these selected botanicals, especially amla and kokum with their high baseline phenolic content, are good bioactive ingredients to counter bacterial contamination of other plant-based foods.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic components include lignin, soluble phenolic compounds, phenolic phytochemicals, and other antibacterial substances, all of which are metabolites of phenylpropane. The accumulation of phenolic components in plants is often part of the defense response against the attack and stress of pathogens, which can be triggered and activated by elicitors [30]. Deenamo et al found that salicylic acid could induce resistance in rubber tree against Phytophthora palmivora by promoting the activities of H 2 O 2 , catalase (CAT), POD and PAL, increasing the content of lignin [31].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant-dependent changes in bacterial proteins involved in, for example, energy metabolism and the tricarboxylic acid cycle, DNA metabolism and fatty acid biosynthesis lead to irreversible changes in bacterial metabolism and eventual death [40]. An important property in the context of the antibacterial activity of polyphenolic compounds is their ability to inhibit the enzyme DNA gyrase, which, in turn, leads to the inhibition of bacterial DNA synthesis [42,43]. Another enzyme essential for the energy metabolism of bacteria is ATP synthase, which undergoes a polyphenol-dependent inhibition, leading to the death of microorganisms [44,45].…”
Section: Journal Of Engineering Sciencementioning
confidence: 99%